The compartmentalized bacteria of the planctomycetes-verrucomicrobia-chlamydiae superphylum have membrane coat-like proteins - Santarella-Mellwig, Rachel; Devos, Damien (PLoS biology, 2010)
Compartmentalized bacteria have proteins that are structurally related to eukaryotic membrane coats, and one of these proteins localizes at the membrane of vesicles formed inside bacterial cells.